Integrating Islamic Economics Principles in Indonesia’s Green-Blue Economy Amidst Digital Transformation and Geopolitical Uncertainty - Aa Hubur (Muttaqien, 2026)
This study examines the green-blue economy concept from an Islamic economics perspective, analyzing how the principles of khalifah (human stewardship of the Earth), maqashid syariah, and the prohibition of israf (waste) and fasad (environmental destruction) can guide sustainable marine and environmental resource management. Using a qualitative approach with literature review and expert interviews, this research identifies opportunities and challenges in integrating digital transformation with green-blue economy practices within an Islamic ethical framework. The findings reveal that Islamic principles align naturally with sustainable development goals, offering a holistic approach that balances economic growth, environmental preservation, and social welfare. For Indonesia as the largest Muslim-majority nation with vast marine resources, integrating Islamic economics principles into green-blue economy policies represents a strategic opportunity to achieve both worldly prosperity and spiritual accountability as mandated in the Qur'an. The study concludes that strengthening international cooperation and developing Islamic-based environmental governance can effectively address challenges posed by geopolitical uncertainty while maintaining alignment with maqashid syariah.